Silicon-doped porous carbon-loaded potassium monatomic solid hydrogen storage material and preparation method thereof

By doping silicon and potassium-loaded single atoms in porous carbon materials, the problem of insufficient hydrogen adsorption capacity of solid hydrogen storage materials is solved, and efficient hydrogen storage and excellent cycling performance are achieved.

CN119191226APending Publication Date: 2024-12-27XIAN TECH UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411236799.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing solid hydrogen storage materials, especially carbon-based materials, still need to be improved in hydrogen adsorption capacity, mainly due to the insufficient surfactant sites of the material, which limits the effective adsorption of hydrogen, and divalent alkaline earth metal calcium during doping. The ability to control the electronic properties of carbon materials is weak, which leads to difficult hydrogen release process and unsatisfactory circulation performance.

Method used

Silicon-doped porous carbon-loaded single-atom solid hydrogen storage material is prepared by high-temperature treatment of tetraethyl silicate and porous carbon, and potassium chloride is impregnated on this basis, and ultrasonic stirring is used to prepare silicon-doped porous carbon materials. Temperature gradient control ensures uniform loading of potassium single atoms and optimizes the pore structure of the material.

Benefits of technology

It significantly improves the hydrogen storage capacity of the material, provides rich active sites, improves the adsorption and desorption efficiency of hydrogen, optimizes the thermodynamic and kinetic characteristics of the hydrogen storage process, and achieves a high specific surface area and a stable hydrogen storage density. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191226A_ABST
    Figure CN119191226A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: adding tetraethyl silicate and porous carbon into deionized water, uniformly stirring, carrying out ultrasonic treatment, standing at room temperature for 6 hours, removing supernate, pre-drying precipitate, heating to 300 DEG C, keeping for 2 hours, putting into a tubular furnace, and carrying out heat preservation for 2 hours under the protection of N2 atmosphere, so as to obtain the silicon-doped porous carbon-loaded potassium monatomic solid hydrogen storage material. Heating at 900 DEG C for 3 hours to obtain a silicon-doped porous carbon material; and dissolving potassium chloride and the silicon-doped porous carbon material in deionized water, stirring at room temperature for 1 hour, standing and precipitating for 4 hours, then carrying out high-speed centrifugal treatment, removing supernate, retaining precipitates, and carrying out heat treatment at 300 DEG C for 3 hours to obtain the hydrogen storage material. The silicon-doped porous carbon material prepared by the invention shows an ultrahigh specific surface area, and provides a large number of active sites for hydrogen adsorption, so that the hydrogen storage capacity of the material reaches 5.2 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-doped porous carbon-loaded potassium single atom solid hydrogen storage material and a preparation method thereof, and is mainly used for solid hydrogen storage materials. Background Art

[0002] The surge in global energy demand has led people to seek cleaner and more sustainable energy development. Hydrogen energy is considered an ideal alternative to traditional fossil fuels due to its high energy density, zero emission characteristics and abundant resource base. However, the large-scale commercial application of hydrogen energy faces many challenges, especially the safety, efficiency and economy of hydrogen storage technology. At present, hydrogen storage technology is mainly divided into three categories: high-pressure gas hydrogen storage, low-temperature liquid hydrogen storage and solid-state hydrogen storage. Solid-state hydrogen storage technology has shown great potential in the field of renewable energy storage because of its higher safety, easy transportation and storage, and suitability for distributed energy systems. Current solid-state hydrogen storage materials, especially carbon-based materials, still need to be improved in hydrogen adsorption capacity. The main problem is that there are insufficient active sites on the surface of the material, which limits the effective adsorption of hydrogen.

[0003] CN117088332A discloses "a nitrogen-doped graphene-loaded alkaline earth metal calcium single atom non-cracking chemical adsorption hydrogen storage material and its preparation method". The method comprises the following steps: fully mixing melamine and graphene, heating to 900°C in a tubular furnace under the protection of a nitrogen atmosphere, then heating at this temperature for 3 hours, and cooling naturally under the protection of a nitrogen atmosphere to obtain nitrogen-doped graphene; adding calcium nitrate and nitrogen-doped graphene to deionized water, stirring evenly at room temperature, making the nitrogen-doped graphene evenly dispersed in the mixed solution, standing at room temperature, removing the supernatant, retaining the precipitate, placing in a vacuum freeze drying box, and freeze-drying at -20°C to obtain a nitrogen-doped graphene-loaded single atom calcium material. The advantages are: the surface area of ​​graphene as a two-dimensional material is mainly the part exposed to the outside, which is convenient for direct loading of metal calcium single atoms. The prepared non-cracking chemical adsorption hydrogen storage material is a surface-induced chemical adsorption, having a medium adsorption strength between physical adsorption and chemical reaction, and can obtain a good hydrogen storage density. The disadvantages are: (1) Although the graphene substrate has a large theoretical specific surface area (>2000m 2 / g), but the surface energy of this two-dimensional material is very large. During the loading process of metal single atoms, stacking is easy to occur, which greatly reduces the theoretical specific surface area and seriously reduces the number of adsorption sites. It is impossible to give full play to the advantages of the high specific surface area of ​​adsorption-type hydrogen storage materials, and the hydrogen storage density is not ideal. (2) The divalent alkaline earth metal calcium has a weak ability to regulate the electronic properties of carbon materials during the doping process, and the interaction between calcium and hydrogen is strong, which makes the release process of hydrogen more difficult, resulting in unsatisfactory cycle performance of hydrogen storage materials. (3) Nitrogen-doped materials have significant chemical incompatibility when loading alkali metal single atoms, especially potassium (K). The electronegativity of nitrogen atoms (3.04) is quite different from that of potassium atoms (0.82), which makes it difficult to effectively match the charge distribution on the surface of nitrogen-doped materials with the electronic configuration of potassium atoms. This incompatibility will hinder the uniform dispersion and stable anchoring of potassium atoms on the surface of the material, thereby affecting the hydrogen adsorption capacity of potassium single-atom hydrogen storage materials. Summary of the invention

[0004] The present invention provides a silicon-doped porous carbon-loaded potassium single-atom solid-state hydrogen storage material with high hydrogen storage density and good cycle stability and a preparation method thereof.

[0005] The technical solution of the present invention is:

[0006] A silicon-doped three-dimensional porous carbon-loaded alkali metal single-atom potassium solid-state hydrogen storage material, wherein the single-atom potassium is loaded on the silicon-doped porous carbon material, and the silicon content in the solid-state hydrogen storage material is 2.02at% and the potassium content is 0.15at%.

[0007] A method for preparing a silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid hydrogen storage material, the specific steps of which are as follows:

[0008] (1) Preparation of tetraethyl silicate-porous carbon dispersion

[0009] Tetraethyl silicate and porous carbon were mixed in a mass ratio of 8:1, deionized water was added, stirred evenly, and ultrasonicated for 30 minutes to form a tetraethyl silicate-porous carbon dispersion;

[0010] (2) Preparation of silicon-doped porous carbon precursor

[0011] The tetraethyl silicate-porous carbon dispersion obtained in step (1) is allowed to stand at room temperature for 6 hours, and after removing the supernatant, the precipitate is placed in a vacuum oven at 100° C. for pre-drying for 4 hours, and the temperature is raised to 300° C. and maintained for 2 hours to obtain a silicon-doped porous carbon precursor;

[0012] (3) Preparation of silicon-doped porous carbon materials

[0013] The silicon-doped porous carbon precursor obtained in step (2) is placed in a tube furnace, heated at 900° C. for 3 hours under the protection of a N2 atmosphere, and naturally cooled to room temperature to obtain a silicon-doped porous carbon material with a high specific surface area and a high porosity;

[0014] (4) Preparation of potassium chloride-silicon doped porous carbon precursor dispersion

[0015] Potassium chloride and the silicon-doped porous carbon material obtained in step (3) are mixed in a mass ratio of 7:10, dissolved in deionized water, and stirred at room temperature for 1 hour using a magnetic stirrer to obtain a uniform potassium chloride-silicon-doped porous carbon precursor dispersion;

[0016] (5) Centrifugation and precipitation collection

[0017] The dispersion obtained in step (4) is allowed to settle for 4 hours, and then subjected to high-speed centrifugation to remove the supernatant and retain the precipitate to obtain a preliminary product of potassium chloride-silicon doped porous carbon;

[0018] (6) Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported by silicon-doped three-dimensional porous carbon

[0019] The potassium chloride-silicon doped porous carbon preliminary product obtained in step (5) is placed in a vacuum oven and heat treated at 300°C for 3 hours. The temperature is gradually increased and maintained using a temperature gradient control to optimize the crystal phase and pore structure of the material. After cooling to room temperature, it is stored in an inert atmosphere to obtain a solid hydrogen storage material of alkali metal single atom potassium supported by silicon-doped three-dimensional porous carbon.

[0020] Furthermore, in step (1), the mass ratio of tetraethyl silicate to deionized water is 8:100.

[0021] Furthermore, in step (4), the mass ratio of potassium chloride to deionized water is 7:1000.

[0022] Furthermore, in step (2), the pre-drying treatment is performed, and the temperature is raised to 300° C. at a heating rate of 10° C. / min.

[0023] Furthermore, when heating in the tubular furnace in step (3), the heating rate to 900° C. is 5° C. / min.

[0024] Furthermore, during centrifugation, the centrifugal speed was 5000 rpm and the centrifugal time was 20 minutes.

[0025] The present invention adopts tetraethyl silicate (C8H 20 O4Si) as a silicon source precursor, porous carbon as a matrix material, and silicon-doped porous carbon material was prepared by high-temperature treatment. Subsequently, the obtained material was immersed in C8H 20In O4Si solution, after stirring, centrifugal separation, heat treatment and other steps, the silicon-doped porous carbon-supported potassium single-atom solid hydrogen storage material was successfully synthesized. It has the following beneficial effects:

[0026] 1) The present invention effectively retains the high specific surface area of ​​the porous carbon material and provides abundant active sites for hydrogen storage and single-atom loading. By precisely controlling the amount of silicon doping, the present invention not only optimizes the microstructure of the material, enhances the diffusion and loading efficiency of potassium single atoms in the pores, but also improves the structural stability of the material under high temperature conditions through stable Si-C bonds.

[0027] 2) Tetraethyl silicate is a precursor for silicon doping, and its molecular structure is large and complex, containing four ethoxy groups. These functional groups significantly limit its diffusion ability in porous carbon, especially in porous carbon materials with smaller pore sizes. In contrast, when doping nitrogen or boron, the commonly used precursor molecules are smaller, the structure is relatively simple, and they usually have higher polarity, which makes it easier for them to interact strongly with the functional groups on the surface of porous carbon through hydrogen bonds. The present invention adopts an ultrasonic-assisted process, which generates strong mechanical vibrations and cavitation effects through the propagation of ultrasonic waves in the liquid, thereby enhancing the physical force between tetraethyl silicate molecules and porous carbon channels. The mechanical vibration of the ultrasound can also effectively break the aggregation state between tetraethyl silicate molecules, reduce the viscosity of the liquid, and enable tetraethyl silicate to be more evenly dispersed in the solution, thereby improving its permeability in the porous carbon structure and ensuring the uniformity and effectiveness of the doping process.

[0028] 3) After silicon atoms are introduced into the porous carbon matrix, silicon-oxygen bonds (Si-OC) are formed. Figure 8The diffraction peak of Si-OC in b proves that it not only improves the chemical stability of carbon materials, but also increases the potassium affinity of materials, and promotes the uniform distribution and firm anchoring of potassium atoms on the surface of carbon materials. Insufficient addition of silicon precursors will lead to uneven distribution of silicon atoms in the carbon matrix, and it is impossible to form an effective Si-OC bond network. In this case, the potassium affinity and electronic structure of porous carbon cannot be significantly improved, which in turn limits the adsorption and storage capacity of potassium atoms. Excessive addition of silicon source will also bring serious consequences. Excessive silicon atoms may aggregate in the porous carbon structure to form excessive silicon oxides or other inactive phases, which will not only block the pores of porous carbon and reduce the specific surface area of ​​the material, but also hinder the diffusion and embedding of potassium ions, thereby significantly reducing the hydrogen storage performance of the material. In contrast, doping atoms such as boron and nitrogen have greater tolerance in doping amount due to their smaller atomic size and different chemical activity. However, the optimal concentration range of silicon doping is relatively narrow, which makes the proper control of silicon source particularly important. Appropriate silicon doping can not only optimize the surface chemical properties of porous carbon, enhance its conductivity and potassium storage capacity, but also maximize the hydrogen storage potential of the material without affecting the pore structure. By controlling the drying temperature of tetraethyl silicate in stages, effective doping of silicon atoms and uniform loading of potassium single atoms were achieved.

[0029] 4) The silicon-doped porous carbon material prepared by the present invention exhibits 2591m 2 The ultra-high specific surface area of ​​​​1.5477 W / g significantly improves the hydrogen storage capacity of the material. This ultra-high specific surface area provides a large number of active sites for the adsorption of hydrogen, making the hydrogen storage capacity of the material reach 5.2wt%, while optimizing the thermodynamic and kinetic characteristics of the hydrogen storage process.

[0030] Through these improvements, the present invention provides a novel silicon-doped porous carbon-loaded potassium single-atom solid-state hydrogen storage material with excellent performance, providing a new solution for the efficient storage and utilization of hydrogen energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 These are scanning transmission electron microscope (STEM) images of potassium single atom materials supported by silicon-doped porous carbon of the present invention (corresponding to Example 1) at different resolutions (a. 100 nm; b. 50 nm; c. 10 nm);

[0032] Figure 2 The scanning transmission electron microscope (STEM) energy spectrum and element distribution diagram of the potassium single atom material supported by silicon-doped porous carbon of the present invention (corresponding to Example 1);

[0033] Figure 3These are scanning electron microscope (SEM) images of the potassium single atom material supported by silicon-doped porous carbon of the present invention (corresponding to Example 1) at different resolutions (a. 20 μm; b. 1 μm);

[0034] Figure 4 is an energy dispersive X-ray spectrum (EDS) diagram of the potassium single atom material supported by silicon-doped porous carbon according to the present invention (corresponding to Example 1);

[0035] Figure 5 : is an energy dispersive X-ray spectrum (EDS) diagram of the potassium single atom material supported by antimony-doped porous carbon of the present invention (corresponding to Example 2);

[0036] Figure 6 is an X-ray diffraction pattern of potassium single atom material supported by silicon-doped porous carbon according to the present invention (corresponding to Example 1);

[0037] Figure 7 is an X-ray diffraction pattern of potassium single atom material supported by antimony-doped porous carbon according to the present invention (corresponding to Example 2);

[0038] Figure 8 The high-resolution X-ray photoelectron spectrum (a) and the high-resolution X-ray sub-spectrum (b) of N1s of the silicon-doped porous carbon-supported potassium single-atom material of the present invention (corresponding to Example 1);

[0039] Fig. 9 is a nitrogen adsorption-desorption isotherm graph of the potassium single-atom material supported by silicon-doped porous carbon according to the present invention (corresponding to Example 1);

[0040] Fig.10 is a pore distribution diagram of potassium single atom material supported by silicon-doped porous carbon according to the present invention (corresponding to Example 1);

[0041] Fig.11 It is a hydrogen adsorption-desorption isotherm graph at liquid nitrogen temperature of the silicon-doped porous carbon-supported potassium single-atom material of the present invention (corresponding to Example 1).

[0042] Fig.12 It is a hydrogen adsorption-desorption isotherm at liquid nitrogen temperature of the antimony-doped porous carbon-supported potassium single atom material of the present invention (corresponding to Example 2). DETAILED DESCRIPTION

[0043] The porous carbon powders used in Examples 1 to Comparative Example 3 and Comparative Example 1 to Comparative Example 6 of the present invention are porous carbons from the same batch.

[0044] Example 1

[0045] S1: Preparation of tetraethyl silicate (C8H 20 O4Si) and porous carbon mixed dispersion

[0046] Add 1g of porous carbon powder (specific surface area 3200m 2 g -1 ), then add 8g tetraethyl silicate (C8H 20 O4Si), stir and mix them thoroughly, then slowly pour 100mL of deionized water into the beaker, stir to make it evenly dispersed; then place the mixed liquid in an ultrasonic processor, and treat it for 30 minutes at a frequency of 40kHz and a power of 200W to enhance the dispersion effect, and finally obtain a dispersion of tetraethyl silicate and porous carbon;

[0047] S2: Preparation of silicon-doped porous carbon powder

[0048] The dispersion of tetraethyl silicate and porous carbon was allowed to settle for 6 hours, the supernatant was removed, and the precipitate was placed in a vacuum oven at 100°C for pre-drying for 4 hours to avoid structural shrinkage or crack formation caused by rapid drying; then, the temperature was increased to 300°C at a rate of 10°C / min, and dried at 300°C for 2 hours to ensure good bonding of tetraethyl silicate and porous carbon, thereby obtaining a preliminary powder product for preparing silicon-doped porous carbon;

[0049] S3: Preparation of silicon-doped porous carbon materials

[0050] The silicon-doped porous carbon powder was placed in a porcelain boat, heated to 900°C at a heating rate of 5°C / min in a tube furnace under N2 atmosphere protection, and heat-treated at this temperature for 3 hours, and then the tube furnace was cooled to room temperature to obtain a silicon-doped porous carbon material;

[0051] S4: Preparation of potassium chloride-silicon doped porous carbon precursor dispersion

[0052] Weigh 1 g of silicon-doped porous carbon material into a beaker, pour 0.7 g of potassium chloride (KCl), and then add 100 mL of deionized water. Stir with a magnetic stirrer at room temperature for 1 hour to ensure the uniformity and stability of the solution. Stir evenly to obtain a potassium chloride-silicon-doped porous carbon precursor dispersion;

[0053] S5: Centrifugation

[0054] The precursor dispersion of potassium chloride-silicon doped porous carbon was allowed to settle for 4 hours, and then treated by high-speed centrifugation (5000 rpm, 20 minutes), the supernatant was removed after centrifugation, and the lower layer of precipitation was retained; and then washed with deionized water for no less than 3 times; a black primary product of potassium chloride-silicon doped porous carbon was obtained;

[0055] S6: Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported on silicon-doped three-dimensional porous carbon

[0056] The black preliminary product of potassium chloride-silicon doped porous carbon was placed in a vacuum oven, heat treated at 300°C for 3 hours, and then cooled to room temperature to obtain a solid-state hydrogen storage material of alkali metal single atom potassium supported by silicon-doped three-dimensional porous carbon.

[0057] In the structural characterization of the alkali metal single-atom potassium material supported by silicon-doped three-dimensional porous carbon obtained in Example 1, the scanning electron microscopy images at different magnifications are as follows: Figure 1 As shown by Figure 1 It can be observed in (a), (b), and (c) that there are a large number of fine pore structures, which shows that doping with silicon and loading potassium atoms does not significantly change the basic morphology and size distribution of carbon. It can be seen that the carbon layer is uniform and orderly, and the microstructure is arranged in layers, with a graphene-like structure; the scanning transmission electron microscope (STEM) energy spectrum and its element distribution diagram are shown in Figure 2. Figure 2 As shown, the presence of C, Si, and K elements and their uniform distribution are clearly shown, proving that this preparation method has successfully introduced potassium atoms into the surface of silicon-doped porous carbon materials; Figure 3 Scanning electron microscope (SEM) images at different resolutions (a.20μm; b.1μm), Figure 3 (a) shows the overall morphology of silicon-doped porous carbon materials. It can be observed that the surface presents an irregular granular structure, the surface is uneven, and shows porous characteristics. This porous structure helps to increase the specific surface area of ​​the material, thereby providing more adsorption sites. Figure 3 (b) shows the structural features at a higher resolution. The microscopic details of the material can be seen, with obvious lamellar structures and tiny pores on the surface. The existence of these lamellar structures and pores is very beneficial for the adsorption of hydrogen because they can provide more active sites, allowing hydrogen molecules to be more easily adsorbed on the surface of the material. At the same time, some unsuccessfully doped single atoms can also be observed on the carbon wall. These isolated atoms failed to be evenly embedded in the carbon matrix. Figure 4 In the energy dispersive X-ray spectrum (EDS) diagram, it can be noted that the silicon and potassium atoms are evenly dispersed, where the distribution positions of silicon and potassium in EDS are the same as those of porous carbon in EDS, indicating the successful doping of silicon atoms and the successful loading of potassium atoms into porous carbon; Figure 6In the X-ray diffraction pattern, a flat and wide peak appeared at 43° 2θ. It can be inferred that the material may be mainly composed of amorphous carbon, which means that the porous carbon matrix after silicon doping has not undergone significant changes in the crystal structure and maintains a relatively disordered carbon-based structure. There are no obvious sharp diffraction peaks in the figure, which indicates that potassium is uniformly embedded in the carbon matrix in the form of single atoms, rather than forming large potassium metal particles or crystal structures. This dispersion is very important for hydrogen storage materials, because uniformly distributed active sites can improve the hydrogen adsorption and desorption properties of the material; it can be seen that the high-resolution X-ray photoelectron spectrum of potassium single atoms supported by silicon-doped three-dimensional porous carbon Figure 8 In (a), silicon and potassium atoms were successfully introduced into the porous carbon, with a relative content of 2.02 at% Si and 0.15 at% K. The main reason why the peak of potassium atoms was not clearly visible was that the potassium atom loading concentration was relatively low, which would inhibit the migration and aggregation of potassium atoms in the material and prevent the formation of crystals, so no obvious characteristic peak of potassium atoms was observed. Figure 8 As can be seen in (b), the energy spectrum can be divided into three peaks, 101.5, 102.6 and 103.5 eV, corresponding to Si-C bond, Si-O-C bond, and Si-O-Si bond, respectively; the nitrogen adsorption and desorption of potassium single atom materials supported by silicon-doped porous carbon are shown in Figure 2. Fig. 9 As shown, it can be seen that the specific surface area of ​​the material is as high as 2591m 2 g -1 The specific surface area is reduced compared with that of porous carbon, indicating that the doped and loaded single atoms fill part of the pores of porous carbon, which is confirmed by the STEM image results. The pore distribution diagram of the hydrogen storage material obtained in Example 1 is shown in Fig.10 As shown, the pore distribution of 2-25 nanometers accounts for a relatively high proportion. Analysis shows that the material is mainly composed of a mesoporous structure, accompanied by a small number of microporous and macroporous structures.

[0058] In the hydrogen storage performance test of the alkali metal single-atom potassium material supported by silicon-doped three-dimensional porous carbon obtained in Example 1, the hydrogen adsorption-desorption isotherm curve at liquid nitrogen temperature is as follows: Fig.11 As shown, when the hydrogen pressure is 70 Pa, the hydrogen adsorption and desorption amount reaches 5.21wt%. At the same time, the adsorption and desorption curves are basically overlapped, which further illustrates the excellent hydrogen desorption and desorption ability of the silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium material prepared by the present invention.

[0059] Comparative Example 2 Antimony-doped porous carbon-supported potassium single atom material

[0060] S1: Preparation of a dispersion of antimony oxide (Sb2O4) and porous carbon

[0061] Add 1g of porous carbon powder (specific surface area 3200m 2 g -1 ), then add 8g of antimony oxide (Sb2O4), stir and mix them thoroughly, then slowly pour 100mL of deionized water into the beaker, stir thoroughly to make it evenly dispersed, and obtain a dispersion of antimony oxide and porous carbon;

[0062] S2: Preparation of antimony oxide-doped porous carbon powder

[0063] The dispersion of antimony oxide and porous carbon was allowed to settle for 3 hours, the supernatant was removed, and then dried at 200° C. for 6 hours to obtain a preliminary powder product of antimony-doped porous carbon;

[0064] S3: Preparation of antimony-doped porous carbon materials

[0065] The antimony-doped porous carbon powder was placed in a porcelain boat, heated to 900°C at a heating rate of 10°C / min in a tube furnace under N2 atmosphere protection, and heat-treated at this temperature for 3 hours, and then the tube furnace was cooled to room temperature to obtain an antimony-doped porous carbon material;

[0066] S4: Preparation of KCl-Sb doped porous carbon precursor dispersion

[0067] Weigh 1 g of antimony-doped porous carbon material into a beaker, pour 0.7 g of potassium chloride (KCl), add 100 mL of deionized water, and stir evenly at room temperature to obtain a potassium chloride-antimony-doped porous carbon precursor dispersion;

[0068] S5: Centrifugation

[0069] The precursor dispersion of potassium chloride-antimony doped porous carbon was allowed to stand for 3 hours to allow for sufficient reaction and precipitation, and then centrifuged in a centrifuge at a speed of 5000 rpm for 20 minutes. After centrifugation, the supernatant was discarded and the lower layer of precipitation was retained; and then washed with deionized water for no less than 3 times to obtain a black primary product of potassium chloride-antimony doped porous carbon;

[0070] S6: Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported on antimony-doped three-dimensional porous carbon

[0071] The black preliminary product of potassium chloride-antimony doped porous carbon was placed in a vacuum oven, heat treated at 300°C for 3 hours, and then cooled to room temperature to obtain a solid-state hydrogen storage material of alkali metal single atom potassium supported by antimony-doped three-dimensional porous carbon.

[0072] In the structural characterization of the antimony-doped three-dimensional porous carbon-supported alkali metal single-atom potassium material obtained in Comparative Example 2, EDS Figure 5 , we can observe the uniform dispersion of silicon and potassium atoms; its X-ray diffraction pattern is as follows Figure 7 The figure shows two broad diffraction peaks at 25.3° and 43°, which correspond to the 002 and 100 planes of the carbon material, respectively. It can be inferred that the material is mainly composed of amorphous carbon, and antimony and potassium are introduced into the porous carbon in the form of single atoms.

[0073] In the hydrogen storage performance test of the antimony-doped three-dimensional porous carbon-supported alkali metal single-atom potassium material obtained in Comparative Example 2, the hydrogen adsorption-desorption isotherm curve at liquid nitrogen temperature is as follows: Fig.12 As shown in the figure, when the hydrogen pressure is 60 Pa, the hydrogen adsorption and desorption amount is only 2.2wt%, and the hydrogen storage performance is poor. This is speculated to be due to the large volume of antimony atoms causing partial blockage or change in the pore structure, resulting in a decrease in specific surface area, and may even introduce stress inside the material, which will significantly reduce the hydrogen storage capacity of the material.

[0074] Comparative Example 3 Silicon-doped porous carbon material

[0075] S1: Preparation of tetraethyl silicate (C8H 20 O4Si) and porous carbon mixed dispersion

[0076] Add 1g of porous carbon powder (specific surface area 3200m 2 g -1 ), then add 8g tetraethyl silicate (C8H 20 O4Si), stir and mix them thoroughly, then slowly pour 100mL of deionized water into the beaker, stir to make it evenly dispersed; then place the mixed liquid in an ultrasonic processor, and treat it for 30 minutes at a frequency of 40kHz and a power of 200W to enhance the dispersion effect, and finally obtain a dispersion of tetraethyl silicate and porous carbon;

[0077] S2: Preparation of silicon-doped porous carbon powder

[0078] The dispersion of tetraethyl silicate and porous carbon was allowed to settle for 6 hours, the supernatant was removed, and the precipitate was placed in a vacuum oven at 100°C for pre-drying for 4 hours to avoid structural shrinkage or crack formation caused by rapid drying; then, it was dried at 200°C for 3 hours to ensure good bonding between tetraethyl silicate and porous carbon, thereby obtaining a preliminary powder product for preparing silicon-doped porous carbon;

[0079] S3: Preparation of silicon-doped porous carbon materials

[0080] The silicon-doped porous carbon powder was loaded into a porcelain boat, heated to 900°C at a heating rate of 10°C / min in a tube furnace under N2 atmosphere protection, and heat treated at this temperature for 3 hours, and then the tube furnace was cooled to room temperature to obtain a silicon-doped porous carbon material.

[0081] In the structural characterization of the silicon-doped porous carbon material obtained in Comparative Example 3, a uniformly dispersed distribution of silicon single atoms can be observed; through the analysis of its XPS graph, it can be inferred that silicon has been successfully doped into the porous carbon, wherein the silicon atom doping content is 1.97 at%.

[0082] In the hydrogen storage performance test of the silicon-doped porous carbon material obtained in Comparative Example 3, hydrogen adsorption-desorption was carried out at liquid nitrogen temperature. When the hydrogen pressure was 70 Pa, the hydrogen adsorption and desorption amount was only 3.1wt%, and the hydrogen storage performance was worse than that of Example 1. The reason for this result is speculated to be mainly due to the lack of active sites and insufficient regulation of the electronic structure. In contrast, the material loaded with potassium achieved higher hydrogen storage performance by enhancing chemical adsorption, optimizing electronic structure, increasing surface energy and improving pore structure. Therefore, potassium loading plays a vital role in improving the hydrogen storage capacity of silicon-doped porous carbon materials.

[0083] Comparative Examples 3-8 Different tetraethyl silicate (C8H 20 O4Si) addition amount

[0084] Comparative Example 3

[0085] The added amount of tetraethyl silicate is 0.6 g, and the rest is the same as in Example 1.

[0086] Comparative Example 4

[0087] The added amount of tetraethyl silicate is 2 g, and the rest is the same as in Example 1.

[0088] Comparative Example 5

[0089] The added amount of tetraethyl silicate is 4 g, and the rest is the same as in Example 1.

[0090] Comparative Example 6

[0091] The added amount of tetraethyl silicate is 6 g, and the rest is the same as in Example 1.

[0092] Comparative Example 7

[0093] The addition amount of tetraethyl silicate is 10 g, and the other steps are the same as those in Example 1.

[0094] Comparative Example 8

[0095] The added amount of tetraethyl silicate is 12 g, and the rest is the same as in Example 1.

[0096] The above set of 6 different tetraethyl silicate (C8H 20 O4Si) addition amount, and other preparation conditions are the same as Example 1. Preparation method of alkali metal single atom potassium supported by silicon-doped three-dimensional porous carbon The parameters of comparative examples 1 to 6 are shown in Table 1 below:

[0097] Table 1 is the parameters of the preparation method of alkali metal single atom potassium supported by silicon-doped three-dimensional porous carbon in comparative examples 1 to 6

[0098]

[0099] The samples prepared in Comparative Examples 1 to 6 were subjected to nitrogen adsorption-desorption tests under isothermal conditions and hydrogen storage performance tests under liquid nitrogen (77K) temperature and 70 Pa hydrogen pressure. The specific surface areas obtained from the tests of Comparative Examples 1 to 6 and the hydrogen adsorption and desorption amounts under 77K temperature and 70 Pa hydrogen pressure are shown in Table 2 below:

[0100] Table 2 is the detection data of alkali metal single atom potassium supported by boron-doped three-dimensional porous carbon in comparative examples 1 to 4

[0101]

[0102] 1. Analysis of the structure and performance of Example 1 of the present invention and its parallel comparative examples 1 to 8

[0103] By comparing the structural characterization and performance test data of Example 1 and Comparative Examples 1-8, it can be concluded that silicon doping and the loading of potassium single atoms significantly improve the structural stability and adsorption capacity of porous carbon materials. Silicon atoms mainly exist in the form of Si-C bonds and Si-O-C bonds (excluding Si-O-Si bonds). These silicon sites can effectively improve the adsorption energy of carbon materials and hydrogen molecules, thereby increasing the number of hydrogen storage sites. Potassium single atoms further enhance the chemical adsorption of hydrogen through their unique chemical properties. The larger atomic radius of potassium helps it to be evenly distributed in porous carbon, and its higher electron supply effect improves the chemical adsorption capacity of the material. Optimization of structure and performance: After doping with silicon and loading potassium single atoms, the porous carbon material of Example 1 still retains an excellent pore structure, and its specific surface area is as high as 2591m 2 / g. This high specific surface area combined with the doping effect of silicon and potassium provides a large number of active sites for the physical and chemical adsorption of hydrogen, thereby significantly improving the hydrogen storage performance. In Comparative Example 2, antimony doping was used to replace silicon, resulting in partial blockage of the pore structure of the material, a decrease in the specific surface area, and a significant decrease in the hydrogen storage performance, which shows that silicon plays an important role in improving the structure and performance of the material. In contrast, in Comparative Example 3, after potassium single atoms were not loaded, the hydrogen storage performance decreased, further proving that the dispersed embedding of potassium into silicon-doped porous carbon enhances the hydrogen storage performance. By comparing and analyzing Comparative Examples 3-8, it can be seen that C8H 20 O4Si is used as a precursor of silicon in porous carbon materials, and its addition amount directly affects the distribution of silicon in the carbon matrix and the formation of pore structure. 20O4Si affects the pore structure. At this time, the low doping concentration of silicon may lead to insufficient formation of Si-C and Si-OC bonds in the carbon matrix. The electronic structure and pore structure of porous carbon materials are not fully optimized, resulting in a low specific surface area, which in turn affects the adsorption capacity of hydrogen. Excessive C8H 20 O4Si can cause excessive aggregation of silicon in the carbon matrix, possibly forming larger silicon oxide clusters or silicon-carbon alloy phases. These clusters may not only block the pores of the carbon matrix, but also destroy the microstructure of the carbon material, thereby significantly reducing the specific surface area and active sites, and ultimately weakening the hydrogen storage performance. 20 When the amount of O4Si added is 8 g as in Example 1, silicon atoms can be evenly dispersed in the pores and surface of the carbon material to form stable Si-C and Si-OC bonds while retaining an ideal pore structure. This uniform doping and pore structure helps to increase the specific surface area of ​​the material and the number of hydrogen storage active sites, thereby achieving optimal hydrogen storage performance.

[0104] II. Effect analysis of a silicon-doped porous carbon-supported potassium single-atom solid hydrogen storage material according to Example 1 of the present invention

[0105] Silicon-doped porous carbon loaded with potassium single atoms exhibits excellent performance in hydrogen storage, and its excellent effect can be attributed to the structural characteristics and element distribution of the material. First, through SEM and STEM analysis, it can be observed that the carbon layer is uniform and orderly, with a graphene-like structure, and has a large number of fine pore structures. These pores provide abundant hydrogen adsorption sites while retaining the basic morphology of the carbon material. The presence of these pores makes hydrogen easier to be adsorbed, thereby enhancing the hydrogen storage capacity of the material. The EDS energy spectrum and element distribution map show the uniform distribution of silicon and potassium elements in the porous carbon material. Potassium single atoms are uniformly loaded on the silicon-doped porous carbon matrix and exist in a non-crystalline form, avoiding the aggregation and crystal formation of potassium atoms, thereby further improving the stability of the material and the hydrogen adsorption efficiency. XPS analysis shows that silicon exists in the form of Si-C, Si-OC and Si-O-Si bonds, which optimizes the electronic structure of the carbon material and increases the hydrogen adsorption capacity. In addition, the broad peak at 43° in the XRD analysis indicates that the material is mainly composed of amorphous carbon, which helps to maintain a high specific surface area and provide more active sites to support the adsorption and desorption of hydrogen. Nitrogen adsorption and desorption tests further confirmed that although the doping of potassium and silicon fills some pores and slightly reduces the specific surface area, it is still as high as 2591m 2 / g, indicating that the material maintains a high porosity and excellent hydrogen storage capacity. The hydrogen adsorption-desorption isotherm at liquid nitrogen temperature shows that the hydrogen adsorption and desorption of the material at a pressure of 70 Pa reaches 5.21wt%, and the adsorption and desorption curves basically overlap, proving its excellent hydrogen storage capacity. The synergistic effect of doping silicon and loading potassium single atoms makes the material show great potential in the field of solid-state hydrogen storage materials.

Claims

1. A silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid-state hydrogen storage material, wherein the solid-state hydrogen storage material is single-atom potassium supported on a silicon-doped porous carbon material, and the silicon content in the solid-state hydrogen storage material is 2.02at% and the potassium content is 0.15at%.

2. A method for preparing the silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid hydrogen storage material as claimed in claim 1, wherein the specific steps are as follows: (1) Preparation of tetraethyl silicate-porous carbon dispersion Tetraethyl silicate and porous carbon were mixed in a mass ratio of 8:1, deionized water was added, stirred evenly, and ultrasonicated for 30 minutes to form a tetraethyl silicate-porous carbon dispersion; (2) Preparation of silicon-doped porous carbon precursor The tetraethyl silicate-porous carbon dispersion obtained in step (1) is allowed to stand at room temperature for 6 hours, and after removing the supernatant, the precipitate is placed in a vacuum oven at 100° C. for pre-drying for 4 hours, and the temperature is raised to 300° C. and maintained for 2 hours to obtain a silicon-doped porous carbon precursor; (3) Preparation of silicon-doped porous carbon materials The silicon-doped porous carbon precursor obtained in step (2) is placed in a tube furnace, heated at 900° C. for 3 hours under the protection of a N2 atmosphere, and naturally cooled to room temperature to obtain a silicon-doped porous carbon material; (4) Preparation of potassium chloride-silicon doped porous carbon precursor dispersion Mix potassium chloride and the silicon-doped porous carbon material obtained in step (3) in a mass ratio of 7:10, dissolve in deionized water, and stir at room temperature for 1 hour to obtain a potassium chloride-silicon-doped porous carbon precursor dispersion; (5) Centrifugation and precipitation collection The potassium chloride-silicon doped porous carbon precursor dispersion obtained in step (4) is allowed to stand for 4 hours, subjected to high-speed centrifugation, the supernatant is removed, and the precipitate is retained to obtain a potassium chloride-silicon doped porous carbon preliminary product; (6) Preparation of solid-state hydrogen storage materials based on alkali metal single-atom potassium supported by silicon-doped three-dimensional porous carbon The potassium chloride-silicon doped porous carbon product obtained in step (5) is placed in a vacuum oven and heat treated at 300° C. for 3 hours. After cooling to room temperature, a solid hydrogen storage material of alkali metal single atom potassium supported by silicon-doped three-dimensional porous carbon is obtained.

3. According to the method for preparing the silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid hydrogen storage material according to claim 2, the mass ratio of tetraethyl silicate to deionized water in step (1) is 8:

100.

4. According to the method for preparing the silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid hydrogen storage material according to claim 2, the mass ratio of potassium chloride to deionized water in step (4) is 7:1000.

5. According to the method for preparing the silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid-state hydrogen storage material as described in claim 2, in step (2), the pre-drying treatment is performed, and the heating rate from the temperature rising to 300° C. is 10° C. / min.

6. According to the method for preparing the silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid hydrogen storage material as described in claim 2, when heating in the tubular furnace in step (3), the heating rate to 900°C is 5°C / minute.

7. According to the method for preparing the silicon-doped three-dimensional porous carbon-supported alkali metal single-atom potassium solid hydrogen storage material as described in claim 2, during centrifugation, the centrifugal speed is 5000 rpm and the centrifugal time is 20 minutes.

Citation Information

Cited By

  • Porous carbon supported fluorine-based functional group hydrogen storage material as well as preparation method and application thereof

    CN120191889A

  • A hydrogen storage material based on porous carbon supported fluorine-based functional groups, its preparation method and application

    CN120191889B